Corporate governance in state-owned companies: effects on performance - Cunha, Thiago Nery da; Marcon, Rosilene; Silva, Jaison Caetano da; Gambirage, Cinara (Revista de Negócios, 2021)
Based on agency theory, this article analyzes the adoption and the strengthening of corporate governance and their resulting on performance of state-owned companies. Therefore, it was employed as empirical context the Brazilian state-owned companies that, by force of law, adopted and started to monitor corporate governance mechanisms. Thus, a longitudinal approach was adopted, between 2013 and 2019, and a panel data model for the analysis of all Brazilian and federal state companies directly controlled by the Union, dependent and not dependent from federal government. To our analysis,Â we employed and original database with longitudinal information at firm level.Â The main results suggest that the adoption and the strengthening of corporate governance mechanisms by state-owned companies can positively influence economic and financial performance and reduce their financial dependence from the government. However, considering the characteristics of public administration, we argue that this effect can be delayed in state-owned companies. This study contributes to the literature in several ways. The study sheds light on the understood aspects of the theme and includes in the discussion the delayed aspect of the effect from corporate governance on state-owned companies. Moreover, the paper also supports managers and formulators of public politics.Â